Paraffin-based phase change microcapsule and preparation method thereof
The paraffin-based phase change microcapsules were prepared by in-situ polymerization, and the modified alumina formed a shell layer and emulsifier was added, which solved the problems of supercooling and low thermal conductivity of paraffin-based phase change microcapsules during the phase change process, improving its Thermal stability, mechanical strength and heat storage properties.
Patent Information
- Application Number
- CN202411625378.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Paraffin-based phase transformation microcapsules are prone to supercooling during the phase transformation process, resulting in hysteresis of heat energy release and absorption, unstable performance, poor structural integrity, and low thermal conductivity, which limits its heat storage performance.
Paraffin-based phase-change microcapsules were prepared by in-situ polymerization method, and a uniform shell layer was formed by modifying alumina to improve thermal stability and thermal conductivity, and paraffin was formed into a uniform emulsified solution through emulsifiers to reduce supercooling.
The thermal stability, mechanical strength and thermal conductivity of phase change microcapsules are improved, the heat storage and leakage prevention are enhanced, the stable combination of paraffin core and shell is achieved, and the overall performance of phase change materials is improved.
Smart Images

Figure CN119119970A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat storage materials, in particular to a paraffin-based phase-change microcapsule and a preparation method thereof. Background Art
[0002] Phase change microcapsules usually have constant melting and crystallization temperatures, have a large energy storage density within a limited temperature change, and can absorb or release a large amount of latent heat during the phase change process. Therefore, as a good heat storage material, they have attracted widespread attention. Among many phase change materials, paraffin has become the most promising phase change material due to its stable chemical properties, non-toxicity, non-corrosiveness, and low price. However, there are still some technical challenges in the practical application of paraffin-based phase change microcapsules, such as: 1) Paraffin is prone to supercooling during the phase change process, which leads to phase change lag, which not only affects the timely release and absorption of thermal energy, but also reduces the thermal impact rate of the phase change material, making the performance of the phase change material unstable; 2) The structural integrity of existing paraffin-based phase change microcapsules is not high, the thermal stability of the wall material and the interface between the core and shell lead to poor heat storage; 3) The thermal conductivity of paraffin itself is low, which limits the rapid transfer of heat.
[0003] Therefore, the present invention urgently needs a new preparation process to solve the above problems. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a paraffin-based phase-change microcapsule and a preparation method thereof, and adopts an in-situ polymerization method to prepare the phase-change microcapsule, thereby solving the problems raised in the above-mentioned background technology.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: According to a first aspect of the present invention, there is provided a method for preparing a paraffin-based phase change microcapsule, comprising the following steps: S1, adding acetic acid solution to the silane coupling agent to adjust the pH to acidic, then adding nano-alumina, ultrasonic treatment, water bath reaction, centrifugation to obtain solid, washing with water to neutrality to obtain a modified alumina aqueous solution; S2, adding an aqueous solution containing an emulsifier to the molten paraffin solution, stirring evenly in a constant temperature water bath to obtain an emulsified solution; S3, slowly dropping the modified alumina aqueous solution into the emulsified solution, and performing in-situ polymerization to obtain the paraffin-based phase change microcapsules.
[0006] The phase change microcapsules prepared by the in-situ polymerization method of the present invention can form a uniform modified alumina shell layer on the outside of the paraffin core, which not only improves the thermal stability of the phase change microcapsules, but also enhances its mechanical strength, effectively preventing the leakage of paraffin during the phase change process. At the same time, the high thermal conductivity of the modified alumina helps to improve the overall thermal conductivity of the microcapsules, thereby solving the problem of low thermal conductivity of the paraffin itself. In addition, the addition of an emulsifier allows the paraffin melt to form a uniform emulsified solution, reducing the supercooling of the phase change microcapsules. In addition, by controlling the core-shell ratio and particle size of the phase change microcapsules, the excellent heat storage and leak-proof properties of the phase change microcapsules can be achieved.
[0007] Preferably, in step S1, an acetic acid solution is added to the silane coupling agent to adjust the pH to 4-5; The silane coupling agent is selected from at least one of KH550, KH560 and KH570; The volume ratio of acetic acid to water in the acetic acid solution is 2-4:1.
[0008] The present application modifies nano-alumina by using a silane coupling agent. The silane coupling agent not only reacts with the hydroxyl groups on the surface of alumina to form a stable covalent bond, thereby improving the chemical stability of the surface of alumina, but also enhances its binding force with the paraffin core, thereby improving the mechanical strength of the phase-change microcapsules. In addition, the silane coupling agent modifies the nano-alumina, thereby reducing the surface energy of the alumina nanoparticles, reducing the aggregation between the particles, improving the dispersibility, and making the prepared phase-change microcapsules have a uniform particle size. At the same time, the silane coupling agent forms a stable protective layer on the surface of the alumina, thereby improving the thermal stability of the phase-change microcapsules.
[0009] Preferably, in step S1, the mass ratio of the nano-alumina to the silane coupling agent is 5-20:1.
[0010] Preferably, in step S1, the ultrasonic treatment time is 1 to 2 hours; The temperature of the water bath reaction is 60-100° C., and the time of the water bath reaction is 4-12 Lh.
[0011] Preferably, in step S2, the emulsifier is selected from at least one of sodium dodecylbenzene sulfonate, styrene maleic anhydride copolymer (SMA), sodium dodecyl sulfate, and hexadecyltrimethyl sodium bromide; The concentration of the emulsifier in the aqueous solution containing the emulsifier is 0.02-0.1 g / mL.
[0012] The present invention reduces the oil-water interfacial tension by adding an emulsifier solution into the paraffin melt, so that the paraffin is better dispersed in water to form a stable emulsion, and at the same time provides conditions for the subsequent preparation of uniform phase change microcapsules.
[0013] Preferably, in step S2, the mass ratio of the paraffin wax to the emulsifier is 5-20:1.
[0014] Preferably, in step S2, the temperature of the constant temperature water bath is 75-100° C., the stirring time is 1-6 h, and the stirring speed is 500-1000 r / min.
[0015] Preferably, in step S3, the rotation speed of the in-situ polymerization is 500-4000 rpm, and the time of the in-situ polymerization is 4-8 hours.
[0016] According to a second aspect of the present invention, a paraffin-based phase change microcapsule is provided, comprising a paraffin core material and a modified alumina shell layer, wherein the core-shell ratio of the paraffin core material to the modified alumina shell layer is 1:2.
[0017] Preferably, the particle size of the paraffin-based phase-change microcapsules is 10-20 μm; The supercooling degree of the paraffin-based phase-change microcapsules is 10-20°C.
[0018] The present invention provides a paraffin-based phase-change microcapsule and a preparation method thereof. It has the following beneficial effects: (1) This scheme provides a method for preparing paraffin-based phase change microcapsules, wherein a modified alumina aqueous solution is added dropwise to an emulsified solution. Since the molten paraffin is evenly dispersed in the emulsified solution, the modified alumina polymerizes in situ around the paraffin to form phase change microcapsules. The obtained phase change microcapsules have uniform particle size and low supercooling.
[0019] (2) This scheme provides a method for preparing paraffin-based phase change microcapsules, which uses modified alumina to prepare phase change microcapsules, thereby improving the thermal stability, mechanical strength and thermal conductivity of the phase change microcapsules. In addition, the silane coupling agent forms a stable protective layer on the surface of alumina, which not only improves the thermal stability but also prevents the leakage of the paraffin core. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic diagram of a scanning electron microscope of a paraffin-based phase change microcapsule prepared in Example 1 of the present invention; Figure 2 A schematic diagram of a scanning electron microscope of a paraffin-based phase-change microcapsule prepared in Comparative Example 1 of the present invention; Figure 3 This is a schematic diagram of a scanning electron microscope of a paraffin-based phase-change microcapsule prepared in Comparative Example 2 of the present invention; DETAILED DESCRIPTION
[0021] In order to better illustrate the content of the present invention, a detailed description is given below in conjunction with specific embodiments.
[0022] Example 1 Preparation of modified alumina: prepare an acetic acid solution with a volume ratio of acetic acid to water of 3:1, add the acetic acid solution to the silane coupling agent KH550 to adjust the pH to 4, then add 8 g of nano alumina, ultrasonically treat for 1 hour, disperse evenly, place in a 60°C water bath to react for 6 hours, centrifuge to obtain the solid, and finally wash with deionized water until neutral to obtain a modified alumina aqueous solution; Preparation of paraffin emulsion: weigh 5 g of paraffin, heat it in a water bath at 75°C to obtain a paraffin melt, weigh 1 g of sodium dodecylbenzene sulfonate and dissolve it in 50 mL of water to obtain an emulsifier solution, then add the emulsifier solution to the paraffin melt, stir it in constant temperature water at 75°C at a speed of 500 r / min for 1 hour to obtain an emulsified solution; Preparation of paraffin-based phase change microcapsules: The prepared modified alumina aqueous solution was slowly added dropwise to the emulsified solution, stirred at 500 rpm for 4 hours, and then washed repeatedly with ethanol three times. The filtered sample was dried in an oven at 40°C for 24 hours to obtain paraffin-based phase change microcapsules with paraffin as the core and modified alumina as the shell. The core-shell ratio of the paraffin-based phase change microcapsules was 1:2, the particle size was 13~16μm, and the supercooling degree was 10~14°C.
[0023] Comparative Example 1 Weigh 5 g of paraffin, heat it in a water bath at 75°C to obtain a paraffin melt, weigh 1 g of sodium dodecylbenzene sulfonate and dissolve it in 50 mL of water to obtain an emulsifier solution, then add the emulsifier solution to the paraffin melt, stir it in constant temperature water at 75°C at a speed of 500 r / min for 1 hour to obtain an emulsified solution; then slowly add the nano-alumina aqueous solution dropwise to the emulsified solution, stir it at a speed of 500 rpm for 4 hours, and then wash it repeatedly with ethanol three times. The filtered sample is dried in an oven at 40°C for 24 hours to obtain paraffin-based phase change microcapsules with paraffin as the core and alumina as the shell, wherein the core-shell ratio of the paraffin-based phase change microcapsules is 1:2, the particle size is 10~15 μm, and the supercooling degree is 13~15°C.
[0024] Comparative Example 2 An acetic acid solution with a volume ratio of acetic acid to water of 3:1 was prepared, and the acetic acid solution was added to a silane coupling agent KH550 to adjust the pH to 4, and then 8 g of nano-alumina was added, and ultrasonic treatment was performed for 1 hour. After being evenly dispersed, the mixture was placed in a 60°C water bath for reaction for 6 hours, and the solid was centrifuged and washed with deionized water until neutral to obtain a modified alumina aqueous solution; 5 g of paraffin was weighed and heated in a 75°C water bath to obtain a paraffin solution; then the modified alumina was added dropwise to the paraffin melt, stirred at a speed of 500 rpm for 4 hours, and then repeatedly washed with ethanol three times. The filtered sample was dried in an oven at 40°C for 24 hours to obtain a paraffin-based phase change microcapsule with paraffin as the core and alumina as the shell, wherein the core-shell ratio of the paraffin-based phase change microcapsule was 1:2, the particle size was 17-20 μm, and the supercooling degree was 13-16°C.
[0025] The surface structures of the paraffin-based phase-change microcapsules prepared in Example 1 and Comparative Examples 1 and 2 are compared. Figures 1 to 3 As shown, according to Figures 1 to 3 By comparison, Figure 1 The surface of the phase change microcapsules prepared by modified alumina is relatively smooth, while the unmodified alumina and the unprepared paraffin emulsion have a certain influence on the morphology of the phase change microcapsules, and the microcapsules present a rough and uneven surface.
[0026] Example 2 Preparation of modified alumina: prepare an acetic acid solution with a volume ratio of acetic acid to water of 3:1, add the acetic acid solution to the silane coupling agent KH550 to adjust the pH to 4, then add 9g of nano-alumina, ultrasonically treat for 1h, disperse evenly, place in a 60°C water bath to react for 6h, centrifuge to obtain the solid, and finally wash with deionized water until neutral to obtain a modified alumina aqueous solution; Preparation of paraffin emulsion: weigh 5 g of paraffin, heat it in a water bath at 75°C to obtain a paraffin melt, weigh 1 g of sodium dodecylbenzene sulfonate and dissolve it in 50 mL of water to obtain an emulsifier solution, then add the emulsifier solution to the paraffin melt, stir it in constant temperature water at 75°C at a speed of 500 r / min for 1 hour to obtain an emulsified solution; Preparation of paraffin-based phase change microcapsules: The prepared modified alumina aqueous solution was slowly added dropwise to the emulsified solution, stirred at 500 rpm for 4 hours, and then washed repeatedly with ethanol three times. The filtered sample was dried in an oven at 40°C for 24 hours to obtain paraffin-based phase change microcapsules with paraffin as the core and modified alumina as the shell. The core-shell ratio of the paraffin-based phase change microcapsules was 1:2, the particle size was 10~14μm, and the supercooling degree was 13~16°C.
[0027] Example 3 Preparation of modified alumina: prepare an acetic acid solution with a volume ratio of acetic acid to water of 3:1, add the acetic acid solution to the silane coupling agent KH550 to adjust the pH to 4, then add 10 g of nano-alumina, ultrasonically treat for 1 hour, disperse evenly, place in a 60°C water bath to react for 6 hours, centrifuge to obtain the solid, and finally wash with deionized water until neutral to obtain a modified alumina aqueous solution; Preparation of paraffin emulsion: weigh 5 g of paraffin, heat it in a water bath at 75°C to obtain a paraffin melt, weigh 1 g of sodium dodecylbenzene sulfonate and dissolve it in 50 mL of water to obtain an emulsifier solution, then add the emulsifier solution to the paraffin melt, stir it in constant temperature water at 75°C at a speed of 500 r / min for 1 hour to obtain an emulsified solution; Preparation of paraffin-based phase change microcapsules: The prepared modified alumina aqueous solution was slowly added dropwise to the emulsified solution, stirred at 500 rpm for 4 hours, and then washed repeatedly with ethanol three times. The filtered sample was dried in an oven at 40°C for 24 hours to obtain paraffin-based phase change microcapsules with paraffin as the core and modified alumina as the shell. The core-shell ratio of the paraffin-based phase change microcapsules was 1:2, the particle size was 13~18μm, and the supercooling degree was 14~18°C.
[0028] Example 4 Preparation of modified alumina: prepare an acetic acid solution with a volume ratio of acetic acid to water of 3:1, add the acetic acid solution to the silane coupling agent KH550 to adjust the pH to 4, then add 11 g of nano-alumina, ultrasonically treat for 1 hour, disperse evenly, place in a 60°C water bath to react for 6 hours, centrifuge to obtain the solid, and finally wash with deionized water until neutral to obtain a modified alumina aqueous solution; Preparation of paraffin emulsion: weigh 5 g of paraffin, heat it in a water bath at 75°C to obtain a paraffin melt, weigh 1 g of sodium dodecylbenzene sulfonate and dissolve it in 50 mL of water to obtain an emulsifier solution, then add the emulsifier solution to the paraffin melt, stir it in constant temperature water at 75°C at a speed of 500 r / min for 1 hour to obtain an emulsified solution; Preparation of paraffin-based phase change microcapsules: The prepared modified alumina aqueous solution was slowly added dropwise to the emulsified solution, stirred at 500 rpm for 4 hours, and then washed repeatedly with ethanol three times. The filtered sample was dried in an oven at 40°C for 24 hours to obtain paraffin-based phase change microcapsules with paraffin as the core and modified alumina as the shell. The core-shell ratio of the paraffin-based phase change microcapsules was 1:2, the particle size was 16~18μm, and the supercooling degree was 14~20°C.
[0029] The heat storage performance and thermal conductivity of the paraffin-based phase change microcapsules prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 2 were tested respectively. The test results are shown in Table 1.
[0030] Table 1 Thermal storage performance and thermal conductivity performance test table of paraffin-based phase change microcapsules
[0031] According to the data in Table 1, as the addition amount of K-Al2O3 increases from 8 g to 11 g, the melting enthalpy of the microcapsules increases first and then decreases. When the addition amount of Al2O3 is 10 g, the melting enthalpy of the paraffin-based phase change microcapsules reaches a maximum value of 165.4 J / g, and the coverage rate of the microcapsules is 16.6% higher than that of Example 1. This may be due to the fact that nano-Al2O3 plays an emulsifying role in the emulsification process of the core material. However, after adding too much nano-Al2O3, the nano-Al2O3 in the reaction system will agglomerate and precipitate, providing a growth nucleus for the prepolymer, so that the prepolymer cannot effectively coat the core material. In addition, the thermal conductivity increases with the increase of modified alumina.
[0032] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing paraffin-based phase-change microcapsules, characterized in that: The following steps are involved: S1, adding acetic acid solution to the silane coupling agent to adjust the pH to acidic, then adding nano-alumina, ultrasonic treatment, water bath reaction, centrifugation to obtain solid, washing with water to neutrality to obtain a modified alumina aqueous solution; S2, adding an aqueous solution containing an emulsifier to the molten paraffin solution, stirring evenly in a constant temperature water bath to obtain an emulsified solution; S3, slowly dropping the modified alumina aqueous solution into the emulsified solution, and performing in-situ polymerization to obtain the paraffin-based phase change microcapsules.
2. The method for preparing a paraffin-based phase-change microcapsule according to claim 1, characterized in that: In step S1, an acetic acid solution is added to the silane coupling agent to adjust the pH to 4-5; The silane coupling agent is selected from at least one of KH550, KH560 and KH570; The volume ratio of acetic acid to water in the acetic acid solution is 2-4:
1.
3. The method for preparing a paraffin-based phase-change microcapsule according to claim 1, characterized in that: In step S1, the mass ratio of the nano-alumina to the silane coupling agent is 5-20:
1.
4. The method for preparing a paraffin-based phase-change microcapsule according to claim 1, characterized in that: In step S1, the ultrasonic treatment time is 1 to 2 hours; The temperature of the water bath reaction is 60-100° C., and the time of the water bath reaction is 4-12 hours.
5. The method for preparing a paraffin-based phase-change microcapsule according to claim 1, characterized in that: In step S2, the emulsifier is selected from at least one of sodium dodecylbenzene sulfonate, styrene maleic anhydride copolymer, sodium dodecyl sulfate, and hexadecyltrimethyl sodium bromide; The concentration of the emulsifier in the aqueous solution containing the emulsifier is 0.02-0.1 g / mL.
6. The method for preparing a paraffin-based phase-change microcapsule according to claim 1, characterized in that: In step S2, the mass ratio of the paraffin wax to the emulsifier is 5-20:
1.
7. The method for preparing a paraffin-based phase-change microcapsule according to claim 1, characterized in that: In step S2, the temperature of the constant temperature water bath is 75-100°C, the stirring time is 1-6 hours, and the stirring speed is 500-1000 r / min.
8. The method for preparing a paraffin-based phase-change microcapsule according to claim 1, characterized in that: In step S3, the rotation speed of the in-situ polymerization is 500-2000 rpm, and the time of the in-situ polymerization is 4-6 hours.
9. A paraffin-based phase-change microcapsule obtained by the preparation method according to any one of claims 1 to 8, characterized in that: It comprises a paraffin core material and a modified alumina shell layer, wherein the core-shell ratio of the paraffin core material to the modified alumina shell layer is 1:
2.
10. The paraffin-based phase-change microcapsule according to claim 9, characterized in that: The particle size of the paraffin-based phase-change microcapsules is 10-20 μm; The supercooling degree of the paraffin-based phase-change microcapsules is 10-20°C.
Citation Information
Patent Citations
Microcapsule of organic phase change energy storage material and preparation method thereof
CN101555401A
Preparation method of inorganic material-coated phase change microcapsule, product prepared thereby and application of product
CN107384328A
Organic phase-change material microcapsules in narrow particle size distribution and preparation method thereof
CN107418519A
Silane coupling agent modified silicon dioxide phase change microcapsule and preparation method thereof
CN110724499A
Phase-change microcapsule based on inorganic shell layer and preparation method and application thereof
CN111621265A
Cited By
Composite phase change film based on liquid metal and PBO fiber and preparation method
CN119490680A
A composite phase change film based on liquid metal and PBO fiber and preparation method thereof
CN119490680B
Preparation process of intelligent temperature-adjusting fabric made of reticular shell microcapsule phase-change material
CN120231236A
Composite phase change film based on solid paraffin and ultra-high molecular weight polyethylene and preparation method
CN120966258A
